The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1186/s13104-016-2344-4
|View full text |Cite
|
Sign up to set email alerts
|

Rapid healing of a patient with dramatic subacute combined degeneration of spinal cord: a case report

Abstract: BackgroundPrevalence of cobalamin deficiency is high especially in older patients and an immediate therapy start is necessary to prevent irreversible neurological damages. Unfortunately, the diagnosis of cobalamin deficiency is difficult and at present, there is no consensus for diagnosis of this deficiency. Therefore, we aim to elucidate a meaningful diagnostic pathway by a case report with an initially misleading medical history.Case presentationA 57 year-old Caucasian man suffering from dramatic myelosis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…Instead, the levels of methylmalonic acid, homocysteine [9], and holotranscobalamin (known as “active B 12 ”) [12] are better biomarkers for diagnosis of vitamin B 12 deficiency. Therefore, a normal serum vitamin B 12 level cannot be used to exclude genuine vitamin B 12 deficiency [13] and damage in this condition. The term “functional vitamin B 12 deficiency” [9] is thus used to take the above considerations into account.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, the levels of methylmalonic acid, homocysteine [9], and holotranscobalamin (known as “active B 12 ”) [12] are better biomarkers for diagnosis of vitamin B 12 deficiency. Therefore, a normal serum vitamin B 12 level cannot be used to exclude genuine vitamin B 12 deficiency [13] and damage in this condition. The term “functional vitamin B 12 deficiency” [9] is thus used to take the above considerations into account.…”
Section: Discussionmentioning
confidence: 99%
“…Different treatments for vitamin B 12 deficiency have been described in the literature [1, 13-16]. To our knowledge, there are as yet no guidelines regarding a therapeutic regimen for patients with SCD.…”
Section: Discussionmentioning
confidence: 99%
“…Index case presented in a sick condition with severe anemia, low platelet and hemolysis, prompting clinician to suspect HELLP syndrome. However low leukocyte count is unusual in HEELP unless disseminated intravascular coagulopathy (DIC) ensue (5).…”
Section: Discussionmentioning
confidence: 99%
“…The finding of a band of thoracic sensory impairment would not be expected with SCD and would be more compatible with TM. A review of the literature identified that both sensory levels and bands of abnormal sensation on the chest have been reported in SCD [3–5]. Although a sensory level might be explained by rare spinothalamic tract involvement [5], there is no satisfactory explanation for the band of abnormal sensation.…”
Section: Discussionmentioning
confidence: 99%
“…Clearly defined sensory level [1] May have thoracic sensory level due to spinothalamic tract involvement [3,5] or band of abnormal sensation on thorax [4,5] Painful, circumferential band of reduced pinprick and temperature at T5eT6 enlargement and no gadolinium enhancement, considered likely TM ( Figure 1A). Brain, thoracic, and lumbosacral spine images showed no abnormalities.…”
Section: Case Presentationmentioning
confidence: 99%